German Culture Introduction Through "Schöne M" Youtube Channel - Trisnawati, Faulanita Pawittri; Pangesti, Isnaini Nur; Rodistya, Zahra Dinda; Zhilulla Dzaikra; Zakiatuz Zahro (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2024)
This article discusses the role of the YouTube channel "Schöne M" in introducing German culture to high school students. With the growing popularity of digital content, platforms like YouTube have become effective means of expanding cultural awareness. In this study the authors used descriptive-analytical research methods. This research explores how "Schöne M" combines engaging and informative approaches in presenting content related to German culture to teenage audiences. Through content analysis and audience responses, this article examines the positive impact of the channel in enriching knowledge of German culture at the high school level. These findings provide valuable insights for educators and policymakers to leverage digital platforms as effective educational tools in introducing foreign cultures to the younger generation.